Bacterial Load in Relation to Physicochemical Parameters and Phytoplankton Abundance of an Urban Pond - Karim, Md Abdul; Begum, ZN Tahmida; Islam, Md Sariful (Bangladesh Journal of Botany, 2012)
Abundance of bacteria and phytoplankton was studied in different months of an urban pond of Dhaka Metropolis from May 2009 to February 2010. Interrelationships among bacteria, phytoplankton densities and the physiochemical properties were also determined. The abundance of bacteria ranged from 5.9×103 to 1.5×107 cfu/100 ml and showed high densities between May and July, while the density of phytoplankton varied from 6.7×104 to 7.5×106 cells/l. Bacterial abundance showed a significant positive correlation with air and water temperature, while phytoplankton showed a significant negative correlation with both of them. Furthermore, bacteria showed a significant positive correlation with conductivity, TDS and alkalinity. Among the physicochemical variables water temperature was significantly correlated with air temperature, pH and alkalinity. Conductivity correlated significantly with TDS and alkalinity. With few exceptions there was inverse relationship between phytoplankton and bacterial abundance in the pond DOI: http://dx.doi.org/10.3329/bjb.v41i1.11077 Bangladesh J. Bot. 41(1): 15-20, 2012 (June)